Dynamically Controllable Two-Dimensional Microvehicle by Coordinated Optical Pulling-Lateral Force - Yuzhi Shi; Hong Luo; Sha Xiong; Tao He; Tongtong Zhu; Qinghua Song; Lei-Ming Zhou; Pin Chieh Wu; Zhanshan Wang; Cheng-Wei Qiu; Xinbin Cheng (IEEE Photonics Journal)
Harnessing exotic optical forces promises a plethora of biophysical applications and novel light-matter interactions. The exotic optical pulling force (OPF) and optical lateral force (OLF) have been studied separately, yet synthesizing both candidates simultaneously remains an unsolved challenge and could offer a more powerful manoeuvre of particles. Here, we report a coordinated scheme to harness these two forces together and present a dynamically controlled two-dimensional (2D) microvehicle. The strategy is to leverage unexplored helicity-dependent features of both forces, while the particle size and incident angle of light can also reverse optical forces. The underlying physics of the pulling-lateral force is beyond the dipole approximation, and can be the combined effect from the linear momentum transfer, spin-orbit interactions, etc. Notably, the ratio of both forces can be dynamically and arbitrarily controlled by the ellipticity of incident light solely. The configured 2D microvehicle provides a nontrivial recipe other than using metastructures which require exquisite designs and subtle fabrication processes.